Studi Pustaka Penerapan Media Puzzle pada Pembelajaran di Sekolah Dasar - Marfilinda, Riri; Akhiyar, Muhammad; Wahyuni, Sisri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Learning media plays an important role in connecting theory with practice, turning abstract concepts into more concrete and interesting experiences, learning media arranges various educational elements into a whole that strengthens students' understanding in an interactive and fun way. The main goal of a puzzle is to solve a challenge by utilizing thinking skills, logic, and sometimes motor skills. This research was carried out to find out the use of puzzle media in teaching in elementary schools. The literature study method in this study, with the help of prisms as a guide for selecting relevant research results. The results of this research include the combination of puzzle media with learning models, combination with other learning media, use based on class, use based on meta lessons, influence on learning in schools. Based on the results of analysis from various relevant research results, the use of puzzle media is often used in elementary school learning and provides positive impacts such as increasing student interest in learning, improving reading skills, increasing student learning achievement, improving learning outcomes, increasing student learning motivation, increasing ability. students' reading and improving students' skills.